Video saliency-recognition by applying custom spatio temporal fusion technique - Warad, Vinay C.; Fatima, Ruksar (IAES International Journal of Artificial Intelligence (IJ-AI), 2024)
Video saliency detection is a major growing field with quite few contributions to it. The general method available today is to conduct frame wise saliency detection and this leads to several complications, including an incoherent pixel-based saliency map, making it not so useful. This paper provides a novel solution to saliency detection and mapping with its custom spatio-temporal fusion method that uses frame wise overall motion colour saliency along with pixel-based consistent spatio-temporal diffusion for its temporal uniformity. In the proposed method section, it has been discussed how the video is fragmented into groups of frames and each frame undergoes diffusion and integration in a temporary fashion for the colour saliency mapping to be computed. Then the inter group frame are used to format the pixel-based saliency fusion, after which the features, that is, fusion of pixel saliency and colour information, guide the diffusion of the spatio temporal saliency. With this, the result has been tested with 5 publicly available global saliency evaluation metrics and it comes to conclusion that the proposed algorithm performs better than several state-of-the-art saliency detection methods with increase in accuracy with a good value margin. All the results display the robustness, reliability, versatility and accuracy.